Puppies for dummies - Hodgson, Sarah (Hoboken,NJ: Wiley, 2006)
An introductory guide for raising a puppy that covers choosing the right dog, house-training, care and nutrition, training for manners, and other puppy-related topics.
Includes index.
5-8.
English.
Keywords: Puppies; Animal babies; Dogs